Fuzzy C-Means and Fuzzy K-Means Algorithms using Fuzzy Functional Dependencies - Reddy Poli, Venkata Subba (International Conference on Fuzzy Theory and Its Applications (Print), 2022)
Fuzzy C-Means (FCM) is c- clustering algorithms for fuzzy dataset of n objects. Fuzzy K-Means (FKM) is k-clustering algorithms of c-clusters. In this paper, we proposed fuzzy c-means clustering algorithm using fuzzy association functional dependencies and Fuzzy K-means MapReduce algorithms using fuzzy association multivalued functional dependencies. We studied fuzzy c-means and fuzzy k-means algorithms in different way. Fuzzy functional dependencies applied on fuzzy c-means clustering and fuzzy k-means clustering. These fuzzy MapReduce algorithms useful quick arrive solutiosn for Clustering. Some examples are given for FCM and FKM.